Presumptive BSE cases with an aberrant prion protein phenotype in Switzerland, 2011: Lack of prion disease in experimentally inoculated cattle and bovine prion protein transgenic mice. Issue 5 (19th April 2018) - Serra, F.; Dudas, S.; Torres, J. M.; Anderson, R.; Oevermann, A.; Espinosa, J. C.; Czub, S.; Seuberlich, T.
Summary: Bovine spongiform encephalopathy (BSE) is caused by different prion strains that are discriminated by the molecular characteristics of the pathological prion protein. In 2011, Switzerland reported two presumptive cases of BSE in cattle with a prion protein phenotype different from previously described strains, and it was unclear whether these findings were related to a transmissible disease and have implications on animal and public health. In this study, brain tissues of these cases were inoculated into transgenic mice expressing the bovine prion protein (BoPrP‐Tg110) and into cattle. Clinical and pathological investigations as well as molecular testing did not provide evidence for the presence of BSE in the Swiss cases after two passages in BoPrP‐Tg110 mice and a challenge period of 3.5 years in cattle. This lack of disease transmission suggests that the Swiss 2011 cases were not affected by a prion disease and were unrelated to the feed‐born BSE epidemic.